Psychometric properties of the empathy questionnaire for children and adolescents in a sample of Tanzanian adolescents - Cherewick, Megan; Dahl, Ronald E.; Leiferman, Jenn A.; Hipp, Emily; Schmiege, Sarah (Frontiers in Psychology, 2022)
Construct definitions of empathy have sought to distinguish between different domains of empathetic capacity that are related to psychological distress or wellbeing. This study aims to validate the psychometric properties of the Empathy Questionnaire for Children and Adolescents (EmQue-CA) and to test for measurement invariance by gender in a sample of 579 very young adolescents (270 boys and 309 girls) ages 9-12 from Tanzania. Exploratory and confirmatory factor analysis were completed to assess the factor analytic structure of the EmQue-CA, indicating a three-factor model fit these data well. Concurrent validity was demonstrated through strong significant correlations with prosocial behavior and generosity measures. Convergent validity indicated the behavioral subdimension of empathy, intent to comfort, was significantly and negatively associated with externalizing behaviors. Measurement invariance by gender was not supported for these data due to configural invariance in covariance between cognitive empathy and intent to comfort latent constructs. These findings confirm the EmQue-CA is an important measure of three dimensions of empathy; affective empathy, cognitive empathy, and behavioral empathy (intent to comfort) in a sample of Tanzanian adolescents.